Peptides and Food Intake - Sobrino Crespo, Carmen; Perianes Cachero, Aránzazu; Puebla Jiménez, Lilian; Barrios, Vicente; Arilla Ferreiro, Eduardo (Frontiers in Endocrinology, 2014)
The mechanisms for controlling food intake involve mainly an interplay between gut, brain, and adipose tissue (AT), among the major organs. Parasympathetic, sympathetic, and other systems are required for communication between the brain satiety center, gut, and AT. These neuronal circuits include a variety of peptides and hormones, being ghrelin the only orexigenic molecule known, whereas the plethora of other factors are inhibitors of appetite, suggesting its physiological relevance in the regulation of food intake and energy homeostasis. Nutrients generated by food digestion have been proposed to activate G-protein-coupled receptors on the luminal side of enteroendocrine cells, e.g., the L-cells. This stimulates the release of gut hormones into the circulation such as glucagon-like peptide-1 (GLP-1), oxyntomodulin, pancreatic polypeptides, peptide tyrosine tyrosine, and cholecystokinin, which inhibit appetite. Ghrelin is a peptide secreted from the stomach and, in contrast to other gut hormones, plasma levels decrease after a meal and potently stimulate food intake. Other circulating factors such as insulin and leptin relay information regarding long-term energy stores. Both hormones circulate at proportional levels to body fat content, enter the CNS proportionally to their plasma levels, and reduce food intake. Circulating hormones can influence the activity of the arcuate nucleus (ARC) neurons of the hypothalamus, after passing across the median eminence. Circulating factors such as gut hormones may also influence the nucleus of the tractus solitarius (NTS) through the adjacent circumventricular organ. On the other hand, gastrointestinal vagal afferents converge in the NTS of the brainstem. Neural projections from the NTS, in turn, carry signals to the hypothalamus. The ARC acts as an integrative center, with two major subpopulations of neurons influencing appetite, one of them coexpressing neuropeptide Y and agouti-related protein (AgRP) that increases food intake, whereas the other subpopulation coexpresses pro-opiomelanocortin (POMC) and cocaine and amphetamine-regulated transcript that inhibits food intake. AgRP antagonizes the effects of the POMC product, α-melanocyte-stimulating hormone (α-MSH). Both populations project to areas important in the regulation of food intake, including the hypothalamic paraventricular nucleus, which also receives important inputs from other hypothalamic nuclei.